How patients would like to improve medical consultations: Insights from a multicentre European study. Issue 1 (January 2016) - Mazzi, Maria Angela; Rimondini, Michela; Boerma, Wienke G.W.; Zimmermann, Christa; Bensing, Jozien M.
Highlights: The sequential mixed-methods ensure validity and trustworthiness of findings. Patients desire to be listened to, taken seriously and treated as person, with no time pressure. Patients consider their own responsibility to speak openly and adhere to treatment plan. Patients emphasize the doctor–patient collaboration for an effective consultation. Patients consider doctors the main responsible for encouraging active patient participation. Abstract: Objective: In a previous qualitative study (GULiVer-I), a series of lay-people derived recommendations ('tips') was listed for doctor and patient on 'How to make medical consultation more effective from the patient's perspective'. This work (GULiVer-II) aims to find evidence whether these tips can be generally applied, by using a quantitative approach, which is grounded in the previous qualitative study. Methods: The study design is based on a sequential mixed method approach. 798 patients, representing United Kingdom, Italy, Belgium and the Netherlands, were invited to assess on four point Likert scales the importance of the GULiVer-I tips listed in the 'Patient Consultation Values questionnaire'. Results: All tips for the doctor and the patient were considered as (very) important by the majority of the participants. Doctors' and patients' contributions to communicate honestly, treatment and time management were considered as equally important (65, 71 and 58% respectively); whereas the contribution of doctors to the course and content of the consultation was seen as more important than that of patients. Conclusions: The relevance of GULiVer-I tips is confirmed, but tips for doctors were assessed as more important than those for patients. Practice implications: Doctors and patients should pay attention to these "tips" in order to have an effective medical consultation.